Estimation of the optimal capacity of energy storage system with consideration to REC policy - Kim, Ha Yang; Kim, Su Duk; Kim, Hyun Goo (IOP Conference Series: Earth and Environmental Science, 2019)
The Korean Government is promoting the distribution of energy storage systems (ESS) that use new and renewable energy sources by applying the Renewable Energy Certificate (REC) weight factor in relation to the new and renewable energy source. This study estimated the optimal ESS capacity by conducting an economic analysis of the REC weight factor. In the case of solar energy, the weight factors of 5.0 and 4.0 were applied to ESSs set to be charged during the specific time of 10:00-16:00 and due to be installed by 2019 and 2020, respectively. The formula for calculating the optimal capacity is E.C=3.64∗P.C-0.49 for a weight factor of 5.0 and 4.0. Here, P.C refers to the solar generator capacity while E.C refers to the optimal ESS capacity. Considering the rate of increase of the charged amount per capacity of the solar power generator installed in Daejeon Metropolitan City, the optimal capacity of the ESS installed in the solar power generator is about 3.6 times that of the solar power generator when the weight factor is 5.0.
Keywords: Energy storage systems; Korean Government; Metropolitan cities; Optimal capacity; Rate of increase; Renewable energy certificates; Renewable energy source; Solar-power generator